A3 2 Steak du Soleil - Bentley, Bobby; Lebidineuse, Leon; McFahn, Ryan (Physics Special Topics, 2023)
In this paper we have explored the possibility of cooking the perfect steak using only solar radiation and have posed the question: How close to the sun would have to be to cook the perfect steak? We found that you would need to be approximately within 220000 km and that is far closer than any human could withstand. We concluded that using solar radiation was not a viable method of cooking a steak.